2015
DOI: 10.1139/cjfas-2014-0517
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic hypoxic zones in Lake Erie compress fish habitat, altering vulnerability to fishing gears

Abstract: Seasonal degradation of aquatic habitats from hypoxia occurs in numerous freshwater and coastal marine systems and can result in direct mortality or displacement of fish. Yet, fishery landings from these systems are frequently unresponsive to changes in the severity and extent of hypoxia, and population-scale effects have been difficult to measure except in extreme hypoxic conditions with hypoxia-sensitive species. We investigated fine-scale temporal and spatial variability in dissolved oxygen in Lake Erie as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 49 publications
0
52
0
Order By: Relevance
“…Our observations and simulations documented similar short‐term upwelling events driven by northeast winds and Ekman transport on the Ohio coast. Kraus et al () monitored DO at 14‐ to 19‐m depth along the Ohio coast and found greater than expected variability at the shallower stations, which they attributed to advection of hypolimnetic water by internal waves. In addition to the short‐term events, we documented a persistent downwelling along the Ohio coast that occurred in July of most years, associated with frequent southwest winds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our observations and simulations documented similar short‐term upwelling events driven by northeast winds and Ekman transport on the Ohio coast. Kraus et al () monitored DO at 14‐ to 19‐m depth along the Ohio coast and found greater than expected variability at the shallower stations, which they attributed to advection of hypolimnetic water by internal waves. In addition to the short‐term events, we documented a persistent downwelling along the Ohio coast that occurred in July of most years, associated with frequent southwest winds.…”
Section: Discussionmentioning
confidence: 97%
“…Rapid changes in bottom DO occur in coastal areas, caused by upwelling or internal waves that result in shoreward advection of hypoxic bottom water. These dynamics can alter fish distribution, cause fish kills, or cause rapid changes in water quality at drinking water plant intakes (Kraus et al, ; Rao et al, ; Ruberg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…, Craig , Campbell and Rice , Kraus et al. ). On the other hand, hypoxia can induce high concentrations of prey, resulting in efficient commercial fishing (Craig ) and efficient feeding opportunities for piscivores (fish that eat other fish), which include many sportfish (Pihl et al.…”
Section: Value Of Ecological Resiliencementioning
confidence: 99%
“…This tactic risks loss of persistence resilience in stressed and changing environments by ignoring habitats that may respond differently to stress (Kraus et al. ) or by concentrating individuals in protected habitats, thus increasing their risk to catastrophic events (McGilliard et al. ).…”
Section: Value Of Ecological Resiliencementioning
confidence: 99%
See 1 more Smart Citation